A 2.4-GHz wireless sensor network for smart electronic shirts integration - Carmo, J. P. (2007)
A typical sensing module is composed of sensors, interface electronics, a radio-frequency (RF) CMOS transceiver and an associated antenna. A 2.4-GHz RF transceiver chip was fabricated in a UMC 0.18 μm CMOS process. The receiver has a sensibility of -60 dBm and consumes 6.3 mW from a 1.8 V supply. The transmitter delivers an output power of 0 dBm with a power consumption of 11.2 mW. Innovative topics concerning efficient power management was taken into account during the design of the transceiver. A solution of individual sensing modules allows a plug-and-play solution. The target application is the integration of a wireless sensor network in smart electronic shirts, for monitoring the cardio-respiratory function and posture.